THE OPTIMAL VOLUME OF ACCOUNTS RECEIVABLE AS A WAY TO IMPROVE THE MANAGEMENT OF CURRENT ASSETS OF STATE ENTERPRISE «NOVATOR» (Development Service Industry Management, 2023)
The amount, composition and structure of current assets of the enterprise determine its effectiveness and efficiency. The primary objective of asset management is to ensure sufficient size and efficient use of assets to support the enterprise's normal functioning.Working capital management policy, in turn, should provide a compromise between the efficiency of the company and the risk of liquidity loss.A significant risk of bankruptcy or lack of funds for conducting profitable activities is possible if accounts receivable, cash, and stocks are kept relatively low. From the other hand, increasing receivables in enterprises can lead to a risk of shortfall of funds, which is often a problem. We believe that strengthening control over receivables and determining their optimal size can help to solve these problems. The optimal amount of receivables is the amount above which is disadvantageous for the enterprise, as there are additional costs. And the optimal maturity of receivables is the maximum period, the excess of which is also associated with the occurrence of losses.Each method for analyzing receivables has its positive and negative features. Therefore, they should be chosen based on the needs of the enterprise and the current situation. The model considered in the article is based on the formula for the dependence of receivables on the credit period, formed by approximating non-linear dependence and further modified. The model provides consideration of trends of previous periods, interdependence of receivables with gross profit, factoring costs values.The analysis of the State Enterprise «Novator» reporting showed a significant increasing in the level of receivables in 2022, which requires special attention to the current assets management. The practical application of the model was tested using data from State Enterprise «Novator». As the result, we calculated the optimal amount of receivables, considering the potential costs related to receivables. The optimal credit period was defined as well.
Keywords: accounts receivable; current assets; optimal level of receivables; optimal credit period